Least-Squares Lowpass Filters with Nonmonotonic Response - Caloba, Luiz P.; Malvar, Henrique S. (IEEE Transactions on Circuits and Systems, 1980)
A new class of all-pole filter functions, derived from the least-squares approximation technique, is introduced. The magintude response is compared with other all-pole filters, like the Butterworth, LSM, and Chebyshev ones. The three subclasses of the new class seem to be a suitable choice for the approvximation function in filter synthesis.